1980
DOI: 10.1093/infdis/141.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Importance of  -Lactamase Inactivation in Treatment of Experimental Endocarditis Caused by Staphylococcus aureus

Abstract: To test the hypothesis that cephalosporins resistant to beta-lactamase are preferred in the treatment of serious staphyloccal infections, the ability of four cephalosporins to eradicate bacteria from the cardiac vegetations of rabbits with experimental endocarditis was examined. Two strains of Staphylococcus aureus were chosen as pathogens: one that rapidly and completely inactivated 50 micrograms of cefazolin in vitro (beta-lactamase-positive) and another that did not inactivate any cephalosporin (beta-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Previous studies (3,30,46) have demonstrated cross-resistance in vivo of many beta-lactams with methicillin for MR CoNS, although a previous retrospective clinical study (26) reported a higher cure rate among patients receiving beta-lactam monotherapy for MR CoNS endocarditis than expected. The superior efficacy of cefpirome compared with that of cefazolin in this study may be due to differences in the affinity for cephalosporinase and the rate of hydrolysis (19) or to differences in the affinity or induction of PBP 2a in the MR subpopulation (34) or in the affinity for PBPs 1 to 3 in the MS subpopulation (11).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies (3,30,46) have demonstrated cross-resistance in vivo of many beta-lactams with methicillin for MR CoNS, although a previous retrospective clinical study (26) reported a higher cure rate among patients receiving beta-lactam monotherapy for MR CoNS endocarditis than expected. The superior efficacy of cefpirome compared with that of cefazolin in this study may be due to differences in the affinity for cephalosporinase and the rate of hydrolysis (19) or to differences in the affinity or induction of PBP 2a in the MR subpopulation (34) or in the affinity for PBPs 1 to 3 in the MS subpopulation (11).…”
Section: Discussionmentioning
confidence: 82%
“…Studies of antibiotic therapy in animal models of S. aureus endocarditis have differed in showing that cefazolin is equivalent (5, 6) or inferior (11) in efficacy to cephalothin. Whereas the REH values of cefazolin and cephalothin by the type B and C ,-lactamases are comparable, the type A and D P-lactamases hydrolyze cefazolin about 25 times more efficiently than they do cephalothin (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In one study, the in vivo effect of the CFZ InE was observed (39) for an MSSA strain, but in a second study using the same strain and animal model, the previous results could not be reproduced (40). High serum CFZ concentrations achieved in the first study and the use of different rabbit strains in the studies were cited as possible causes for these discrepancies (39,40).…”
Section: Discussionmentioning
confidence: 99%